Obsidian provenance analyses at Göytepe, Azerbaijan: Implications for understanding Neolithic socioeconomies in the southern Caucasus*. (29th January 2019) - Nishiaki, Y.; Maeda, O.; Kannari, T.; Nagai, M.; Healey, E.; Guliyev, F.; Campbell, S.
Abstract : This study presents a provenance analysis of the Neolithic obsidian assemblages from the early to mid‐sixth millenniumbc settlement at Göytepe, Azerbaijan. The study is unique in that (1) it involves a complete, non‐selected obsidian assemblage (901 artefacts) from one particular area of the site; (2) the material is derived from a well‐stratified sequence of 10 securely radiocarbon‐dated architectural levels; and (3) the use of an extraordinarily wide range of sources (more than 20) was identified by provenance analysis using energy‐dispersive X‐ray fluorescence. The results reveal a previously unknown diachronic change in obsidian use in the region, suggesting the occurrence of significant socioeconomic changes during the Late Neolithic of the southern Caucasus.